Влияние фланцевого соединения и возникающих в нем усилий на ресурсные показатели ЦСД турбины К-200-130 - Черноусенко, Ольга Юрьевна; Пешко, Виталий Анатольевич (НТУ "ХПИ", 2016)
Предложено совершенствование модели корпуса цилиндра среднего давления турбины К-200-130 путём приближения конструктивной формы фланцев горизонтального разъёма к реальному виду и учёта, возникающих в шпилечных соединениях, усилий. Показано, что данное мероприятие уменьшает уровень интенсивности напряжений, возникающих в корпусе турбины при пусках из различных тепловых состояний. Учёт усилий возникающих во фланцах показал значительное влияние затяжки шпилек на напряжённо-деформированное состояние корпуса турбины. Эти усилия, в некоторой мере, компенсируют усилия со стороны давления и разности температурных полей и способствует улучшению ресурсных показателей корпуса.

It is proposed to improve the model of the casing for the intermediate pressure cylinder of the К-200-130 turbine by making the structural type of the flanges of horizontal connector similar to the real type, taking into consideration the stresses that arise in doweled joints. It was shown that the transition from the model with the flanges of a simplified type to the model of a real type is accompanied both by the total decrease in the intensity of stresses inside the casing at all hot starts and the appearance of new stress concentrators on the outer part in the places of transition from the flanges to thin-wall casing elements. The registration of stresses that arise in the flanges showed a considerable influence of pin tightening on the mode of deformation of the turbine casing. These stresses compensate to some extent the stresses caused by pressure and temperature field differences and contribute to the improvement of the life indices of the casing, in particular the acceptable number of all hot starts, cyclic and statistical failures, and the residual life of the IPC casings of the К-200-130 turbine.
Influence of the flange connection and the stresses arising in It on the life Indices of the intermediate-pressure cylinder of К-200-130 turbine
Keywords: паровая турбина; тепловое состояние; напряжённо-деформированное состояние; остаточный ресурс; steam turbine; thermal state